Luwes and Philosophical: Dewaruci Puppet Performance in Suryomentaram’s Kasampurnan Concept - Zustiyantoro, Dhoni; Nuryatin, Agus; Supriyanto, Teguh; Doyin, Mukh (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2022)
This study explores the performance of Ki Manteb Soedarsono’s Dewaruci and Bima characters in it. As a carangan play (contemporary), Dewaruci is the most popular play. The purpose of this study is to describe the elements of Dewaruci puppet performance and how the concept of kasampurnan in Javanese cultural psychology was initiated by Suryomentaram (1892-1962). This is qualitative research with a psychological approach using the method of reading, taking notes, and studying literature. The data in a form of performances and texts were collected from Dewaruci scripts and puppet videos on Kanal Seni Gelar YouTube channel. We combine Dewaruci script with the puppeteer Ki Manteb and other sources, in addition, to conduct a critical analysis to identify kasampurnan life concept that Bima does in this play from Suryomentaram’s perspective. The result of the study shows that the Dewaruci puppet show by Ki Manteb has the advantage of being flexible and able to adapt to the context and needs of the audience. The concept of kasampurnan in Dewaruci as a representation of Javanese culture can be explained from the perspective of Suryomentaram indigenous psychology. This finding contradicts previous psychological analyses in literature and art. Previous psychology research used the theory of Sigmund Freud, C. G. Jung, and Alfred Adler. However, we argue that the theory cannot always explain the cultural context because of cultural differences between theory and objects. Therefore, this research is relevant in the spirit of science decolonization to see humans in Javanese culture according to their context and culture.